Development of Barkhausen Noise Method for Residual Stress Evaluation In Steels - Osama Hamed Abd Alsalam Alasamar (African Journal of Advanced Pure and Applied Sciences, 2024)
A significant amount of the hysteresis in the magnetization of a ferromagnetic material takes place with a random chain of discontinuous motions of magnetic domain walls. This gives rise to what is called Magnetic Barkhausen Noise (MBN). These noise events are analysed statistically during the detection of the random voltage monitored on a pickup coil through the magnetization of the material. The study of Magnetic Barkhausen Noise (MBN) can provide information on the interaction between stress and domain walls arrangements, or composition or microstructure. The method is a complementary Non-Destructive Testing (NDT) procedure to that of eddy-current inspection. This article will focus on the effect of stress on Magnetic Domain configuration, and how this is reflected in the Magnetic Barkhausen Noise (MBN) signal, and how it can be analyzed by using a diversity of parameters. Simultaneously, residual stresses and dislocations take part in an important function in the Magnetic Barkhausen Noise (MBN) investigation, complementary the analysis and adding to the competitiveness of Magnetic Barkhausen Noise (MBN) as a Non-Destructive Testing (NDT) technique for ferromagnetic materials. This article will also focus on Grinding, Grinding Burn and its various types, and compare with other residual stress detection methods particularly the X–Ray Diffraction Method (XRD).